Comprehending Sentences With the Body: Action Compatibility in British Sign Language?. (3rd August 2016) - Vinson, David; Perniss, Pamela; Fox, Neil; Vigliocco, Gabriella
Abstract: Previous studies show that reading sentences about actions leads to specific motor activity associated with actually performing those actions. We investigate how sign language input may modulate motor activation, using British Sign Language (BSL) sentences, some of which explicitly encode direction of motion, versus written English, where motion is only implied. We find no evidence of action simulation in BSL comprehension (Experiments 1–3), but we find effects of action simulation in comprehension of written English sentences by deaf native BSL signers (Experiment 4). These results provide constraints on the nature of mental simulations involved in comprehending action sentences referring to transfer events, suggesting that the richer contextual information provided by BSL sentences versus written or spoken English may reduce the need for action simulation in comprehension, at least when the event described does not map completely onto the signer's own body.